An ATRActive future for differentiation therapy in AML. Issue 4 (July 2015) - Johnson, Daniel E.; Redner, Robert L.
Abstract: The success of all-trans retinoic acid (ATRA) therapy in acute promeylocytic leukemia (APL) has spawned numerous attempts to translate the paradigm of differentiation therapy to non-APL acute myelocytic leukemia (AML). However, the results of clinical trials have been overall disappointing. In this review we discuss the mechanism of retinoic acid signaling and the results of major clinical trials that have attempted to incorporate ATRA into AML regimens. We discuss recent evidence that indicate that the retinoic acid signaling pathway may be dysfunctional in AML. Preliminary studies suggest that targeting the pathways that modify retinoic acid receptor activity may reactivate the dormant retinoic acid-signaling pathway. Such strategies may revive the ability of ATRA to induce myeloid differentiation and apoptosis in non-APL AML.